Popular and unpopular infectious agents linked to primary biliary cirrhosis - Koutsoumpas, Andreas L. (Auto Immun Highlights, 2012)
Primary biliary cirrhosis (PBC) is a progressive cholestatic liver disease characterized by the autoimmune destruction of the biliary epithelial cells of the small and medium-size bile ducts. The disease affects middle aged women and usually affects more than one member within a family. The pathognomonic serological hallmark of the disease is the presence of circulating anti-mitochondrial antibodies, and disease-specific anti-nuclear antibodies. Susceptibility genes and environmental risk factors such as infections and smoking have been reported as important for the development of the disease. Among the environmental agents, infectious triggers are the best studied. Most of the work published so far has investigated the role of infections caused by Novosphingobium aromaticivorans and Escherichia coli. This review will discuss the popular and unpopular infectious agents causatively linked to PBC. It will also examine reports investigating the epidemiological aspects of the disease and their direct or indirect implications to bacterial-induced PBC.